Alport syndrome and pregnancy: Good obstetric and nephrological outcomes in a pregnant woman with homozygous autosomal recessive Alport syndrome. Issue 3 (2nd December 2015) - Nishizawa, Yoko; Takei, Takashi; Miyaoka, Tokiko; Kamei, Daigo; Mochizuki, Toshio; Nitta, Kosaku
Abstract: We describe the course of pregnancy in a 27‐year‐old woman with homozygous autosomal recessive Alport syndrome. Genetic analysis revealed a homozygous COL4A4 mutation in exon 36 (c.3307G > A) with p.G1102R inherited from her parents (who were parallel cousins) 1 year before conception. Before pregnancy, the patient's renal function and blood pressure were normal, and her urinary protein excretion was below 2 g/day. The pregnancy course was uneventful in the first and second trimesters. She was detected to have nephrotic‐range proteinuria during the third trimester, but was observed closely on an outpatient basis without any medications, as her general condition was good, her renal function and blood pressure remained stable, and the fetal well‐being was maintained. At 39 +0 weeks of pregnancy, she vaginally gave birth to an appropriate‐birthweight infant and her urinary protein excretion returned to pre‐pregnancy level. This is the first report of pregnancy in a patient with autosomal recessive Alport syndrome with good obstetric and nephrological outcomes in the absence of any treatment or hospitalization.